(untitled) (Journal of Applied Oral Science, 2022)
Objective: Since the transmittance of ceramics can influence the degree of conversion (DC) of resin cements, ceramics composition and shade should be considered in the selection of resin cement. This in vitro study aimed to evaluate the effect of the transmittance of different composition, opacities and shades of ceramics on the degree of conversion of two dual-cured resin cements. Methodology: Sixty discs were prepared from low translucency (LT) and medium opacity (MO) lithium disilicate ceramic, and zirconia ceramic (Z). Each group was subdivided into 5 subgroups (n=4) in shades A2, A3.5, B2, C2 and D3. The transmittance measurement was performed in a spectrophotometer. The Variolink II and Rely X U200 resin cements were photoactivated by LED (1400 mW/cm2) for 40 s through the ceramic discs and without the discs (control group). The DC was measured with infrared FTIR spectroscopy, immediately after light activation. Data were analyzed with Kruskall-Wallis and one-way ANOVA, following post-hoc comparisons by Tukey test and Pearson’s correlation test (P<0.05). Results: LT ceramic exhibited higher transmittance values compared to MO and Z ceramics. LTA2 and LTB2 showed statistically higher transmittance values compared to MOA2, MOA3.5 and ZA3.5. For Variolink II, the ceramic interposition did not influence the DC, since there were no statistical differences between groups with ceramic interposition and the control group. For Rely X U200 cement, the interposition of some ceramics types/shades (LTA3.5, MOA2, MOA3.5 and ZA3.5) significantly decreased the DC values compared to control group. A positive correlation was found between the ceramic transmittance and DC values of both tested cements. Conclusions. The transmittance and DC values of the cements were influenced by composition and shades of the ceramics. The higher the transmittance of ceramics, the higher the DC values for both cements.